Celebrating Adam Watkins First Birthday in Watkins' Backyard - Watkins, Howard::::::::: (1979)
Ruth Wall, ?Fran Calloway, ?, Frances Kamp, Christine Watkins, Stephanie Lieberman, Leroy Cordova, Doug Broten, Laurie Leifer holding Gregory Leifer, ?? Watkins TV video of Adam Watkins' birth